Iranian Health Information Technology Acceptance Model (IHITAM) from Users’ Views - Farzandipour, Mehrdad (Acta Inform Med, 2019)
INTRODUCTION: Information technology (IT) is an important component of medical informatics. Information needs to be accepted by users to function effectively. At different ages and from different views, several models have been proposed and used to show factors affecting users’ IT acceptance. However, such models are in need of frequent revision and development due to variable conditions. AIM: The present research aims to design a new health IT acceptance model from Iranian users’ views. The research aims both to design a model for status quo by reviewing previous models and consider features of Iranian users. METHODS: This is a correlative, cross-sectional study. Firstly, the primary model was presented by studying important IT acceptance models. Then, a structured questionnaire was designed and, after confirmation of validity and reliability of the questionnaire, it was given to users of information and health IT systems in different wards of hospitals in Iran. Data were analyzed by SPSS and Lisrel and the final model was designed by structural equations. RESULTS: The model showed that there are six key factors which are effective on attitude and use intention including performance expectancy, observability, effort expectancy, facilitating conditions, empowerment and subjective norms via three interface factors of perceived usefulness, perceived ease of use, self-efficacy. The size of technology use is an important factor in technology acceptance and application as well. CONCLUSION: The present model has more details compared to the other models and can show a new image of important factors in technology acceptance and their relationships.